Analytical Method Validation and Determination of Free Drug Content of 4-n-Butylresorcinol in Complex Lipid Nanoparticles Using RP-HPLC Method - Rini Dwiastuti; Marchaban Marchaban; Enade Perdana Istyastono; Florentinus Dika Octa Riswanto (Universitas Gadjah Mada, 2018)
Lipid nanoparticles, one of nanoparticle technology results has been developed both as a drug delivery system and as a research object. Complex lipid nanoparticle, in the drug delivery system development, has an advantage due to its less toxicity. It is important to develop a validated analytical method to determine the drug content in the system of nanoparticle lipid. This research aimed to develop a valid RP-HPLC method to determine free drug content of 4-n-butylresorcinol in the liposome matrix followed by the determination of the encapsulation efficiency (EE%). A system of the RP-HPLC method has been developed using a column of C18 and methanol-redistilled water-glacial acetic acid 79:20:1 (v/v) as the mobile phase with pH maintained at 2.1–2.6. This method was validated in the parameters of selectivity, sensitivity, linearity, accuracy, and precision. During 30 days of storage, the complex lipid nanoparticle system showed the increase in the EE% value during storage time.